Reconstitution and purification of flagellar filaments from Caulobacter crescentus. - Sheffery, M (1977)
Filaments from isolated flagella of Caulobacter crescentus have been purified by successive dissociation and reconstitution. After the second and third reconstitutions from subunits in 0.8 M sodium citrate, filament preparations contained only two proteins, flagellin A (26,000 daltons) and flagellin B (28,000 daltons). There was some enrichment for flagellin A during reconstitution by this procedure, since isolated flagella contained flagellin A and flagellin B in a ratio of approximately 3.8:1 and filaments after the third reconstitution contained the two proteins in a ratio of 5.0:1.